Solve all your doubts with Teachoo Black (new monthly pack available now!)

Formulae based

Inverse Trigonometry Formulas

Example 3 (i) Important Deleted for CBSE Board 2023 Exams

Ex 2.2,1 Deleted for CBSE Board 2023 Exams You are here

Ex 2.2, 2 Important Deleted for CBSE Board 2023 Exams

Example 8 Deleted for CBSE Board 2023 Exams

Ex 2.2, 12 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 14 Important Deleted for CBSE Board 2023 Exams

Example 4 Deleted for CBSE Board 2023 Exams

Ex 2.2, 3 Deleted for CBSE Board 2023 Exams

Misc. 8 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 4 Important Deleted for CBSE Board 2023 Exams

Ex 2.2, 15 Important Deleted for CBSE Board 2023 Exams

Example 13 Important Deleted for CBSE Board 2023 Exams

Misc. 14 Deleted for CBSE Board 2023 Exams

Misc 17 (MCQ) Deleted for CBSE Board 2023 Exams

Misc. 13 Important Deleted for CBSE Board 2023 Exams

Example 10 Important Deleted for CBSE Board 2023 Exams

Misc. 3 Deleted for CBSE Board 2023 Exams

Misc. 4 Important Deleted for CBSE Board 2023 Exams

Misc 12 Important Deleted for CBSE Board 2023 Exams

Misc 16 (MCQ) Important Deleted for CBSE Board 2023 Exams

Last updated at Dec. 24, 2021 by Teachoo

Ex 2.2, 1 3sin-1 π₯ = sin-1 (3π₯ β 4π₯^3), π₯β [β1/2,1/2] Solving R.H.S sin^(β1) (3π₯ β 4π₯^3) Putting x = sin π = sin^(β1) (3 sin π β 4 γ"sin" γ^3π) = sin^(β1) (sin 3π ) = 3π = 3 γπππγ^(βπ) x Now, x = sin π sinβ1 x = π (sin 3x = 3 sin x β 4 γπ ππγ^3x) (γπ ππγ^(β1) (sin x) = x ) = L.H.S Hence, proved.